2012
DOI: 10.1007/s00253-011-3851-9
|View full text |Cite
|
Sign up to set email alerts
|

Perstraction of intracellular pigments by submerged cultivation of Monascus in nonionic surfactant micelle aqueous solution

Abstract: "Milking processing" describes the cultivation of microalgae in a water-organic solvent two-phase system that consists of simultaneous fermentation and secretion of intracellular product. It is usually limited by the conflict between the biocompatibility of the organic solvent to the microorganisms and the ability of the organic solvent to secret intracellular product into its extracellular broth. In the present work, submerged cultivation of Monascus in the nonionic surfactant Triton X-100 micelle aqueous sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 40 publications
(53 reference statements)
4
53
0
Order By: Relevance
“…Extractive fermentation exports Monascus pigments from cell interiors into its extracellular broth (Hu et al 2012;Kang et al 2013b). An interesting phenomenon was that orange Monascus pigments were accumulated intracellularly during submerged culture of Monascus anka in an aqueous solution while both extracellular and intracellular yellow ones were produced during extractive fermentation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extractive fermentation exports Monascus pigments from cell interiors into its extracellular broth (Hu et al 2012;Kang et al 2013b). An interesting phenomenon was that orange Monascus pigments were accumulated intracellularly during submerged culture of Monascus anka in an aqueous solution while both extracellular and intracellular yellow ones were produced during extractive fermentation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, extractive fermentation of intracellular Monascus pigments carried out successfully in nonionic surfactant Triton X-100 micelle aqueous solution (Hu et al 2012). It was observed that the profile of Monascus pigments was affected by both pH of the culture medium and extractive fermentation (Kang et al 2013a).…”
Section: Introductionmentioning
confidence: 97%
“…The hydrophobic Monascus pigments are majorly accumulated intracellularly in conventional submerged aqueous culture. Recently, nonionic surfactant micelle aqueous solution is further developed for extractive fermentation of intracellular Monascus pigments [9], in which secretion of intracellular product and regulation of secondary microbial metabolites are fulfilled at the same time [10,11]. Especially, extractive fermentation in the nonionic surfactant Triton X-100 micelle aqueous solution with high MSG (monosodium glutamate) concentration produces the high color hue of red Monascus pigment derivates with MSG (monosodium glutamate) residue (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…In submerged fermentation, Monascus pigments are mainly synthesized and accumulated in the mycelia (Chen and Johns 1993), in which two orange pigments (rubropunctatin and monascorubrin), two red pigments (rubropunctamine and monascorubramine) and two yellow pigments (monascin and ankaflavin) have been identified as the main intracellular pigments (Feng et al 2012). However, accumulation of the intracellular pigments trapped in the mycelia became a significant challenge for the higher productivity of the total pigments due to the feedback inhibition and production degradation (Hu et al 2012a; Chen et al 2015). …”
Section: Introductionmentioning
confidence: 99%